Pengaruh Bermain Game “Mobile Legends: Bang Bang” Terhadap Perilaku Kekerasan - Jorgi, Bayu; Yanto, Yanto; Maryaningsih, Maryaningsih (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Mobile Legends: Bang Bang is a mobile video game with the multiplayer online battle arena (MOBA) genre developed and published by Moonton, a subsidiary of Byte Dance. Released in 2016, this game is increasingly popular throughout the world, especially in the Southeast Asia region. This research was motivated by the influence of playing the mobile legends game: Bang Bang on violent behavior. This research aims to determine the effect of playing mobile legends: bang bang on violent behavior among RW boarding school children in Muara Bangka Hulu District, Bengkulu Province. The type of research used is quantitative methods. The data analysis method used is hypothesis testing. The results of this study show that there is a significant influence between playing online games which has a significant influence on violent behavior in the mobile legends game: bang bang. This is proven by the results of the f test showing that the f-count value is greater than the f-table (13.576> 3.26) with a significance level of (0.001 < 0.05.